ATTENTION DEFFICIT AND HYPERACTIVITY (ADHD) PENELITIAN QUASY-EXPERIMENTAL DI SEKOLAH ANAK BERMASALAH (SAB) HARAPAN AISYIYAH MOJOKERTO - PUSPITANINGSIH, DWIHARINI (HOSPITAL MAJAPAHIT (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT), 2010)
Attention Deficit and Hyperactivity Disorder (ADHD) represents disparity which is marked by 3 main symptoms of emotion; that is inattention, hyperactivity, and impulse behavior. Brain gym plays a part in the balance of left and right brain so that the balance of emotion also will be reached. However, the influence of brain gym on behavioral changes in children with ADHD has not known yet clearly. The goal of this research is to analyze the influence of brain gym on behavioral changes in ADHD children.Quasy experimental pre-post test design was used in this study. 14 respondents (ADHD children) in SAB Harapan Aisyiyah Mojokerto were selected and divided into 2 groups of 7 experiment and control group. The intervention was brain gym for a month (3 times a week). There are two variables used here; they were brain gym as independent variable and behavioral changes of ADHD as dependent variable was. Data were taken from questionnaire and observation of respondents. Then, the data were presented as descriptive statistics and statistical analysis was carried by using Wilcoxon Signed Rank Test with significance level = 0,05 and Mann-Whitney Test with significance level = 0,05 and analyzed by using software SPSS 12.0.Finally, the results showed that there was influence of brain gym to behavioral changes of ADHD children (p=0,007). In conclusion, routine barin gym can cause behavioral changes in ADHD children as marked by better attention, more controlled activity, and decrease of impulsive behaviour. Further research is required by involving larger number of respondents, longer than a month and better measurement so that the result PENGARUH SENAM OTAK TERHADAP PERUBAHAN PERILAKU ANAK will be more accurate.Key words: brain gym, behavioral changes, children with ADHD.